Suicidal tendencies and its association with psychoactive use predictors among university students in Uganda: A cross-sectional study - Wesonga, Sheila; Osingada, Charles; Nabisere, Allen; Nkemijika, Stanley; Olwit, Connie (African Health Sciences, 2021)
Background: Globally, suicide is one of the leading causes of death, and approximately 80% of all suicides occur in lowand middle-income countries. Younger people in Africa are at a higher risk of suicide than others. Objective: To describe the prevalence and factors associated with suicidal tendencies among undergraduate university students using alcohol and other psychoactive substances. Methods: Convenient sampling was used to identify 400 students who participated in the study. Socio-demographic and Mini-International Neuropsychiatric Interview tools were used to obtain information. Data were analyzed using SAS 9.4 and presented in descriptive and inferential statistics. Results: Among the respondents, 80% were male, and 85% were using marijuana. 6.3% had suicidal tendencies. Respondents from the northern region had more suicidal tendencies than other regions, and unemployed students had more suicidal tendencies than those employed. After multivariate analysis, being abusive and dependent on other psychoactive substances was associated with suicidality. And having dependence on both alcohol and other psychoactive substances was associated with suicidality. Conclusion: Suicidality screening and psychosocial support should be provided to this vulnerable population. Efforts There is a need to strengthen, implement more effective preventive strategies to reduce the use of alcohol and other psychoactive substances.
Keywords: Suicidal tendencies; Psychoactive use; University students; Uganda